Skeletal Muscle Function and Its Relation to Exercise Tolerance in Chronic Heart Failure - Harrington, Derek; Anker, Stefan D; Chua, Tuan Peng; Webb-Peploe, Katharine M; Ponikowski, Piotr P; Poole-Wilson, Philip A; Coats, Andrew J.S (Journal of the American College of Cardiology, 1997)
Objectives. This study sought to define the relation between muscle function and bulk in chronic heart failure (HF) and to explore the association between muscle function and bulk and exercise capacity. Background. Skeletal muscle abnormalities have been postulated as determinants of exercise capacity in chronic HF. Previously, muscle function in chronic HF has been evaluated in relatively small numbers of patients and with variable results, with little account being taken of the effects of muscle wasting. Methods. One hundred male patients with chronic HF and 31 healthy male control subjects were studied. They were matched for age (59.0 ± 1.0 vs. 58.7 ± 1.7 years [mean ± SEM]) and body mass index (26.6 ± 0.4 vs. 26.3 ± 0.7 kg/m2). We assessed maximal treadmill oxygen consumption (V̇o2), quadriceps maximal isometric strength, fatigue (20-min protocol, expressed in baseline maximal strength) and computed tomographic cross-sectional area (CSA) at midthigh. Results. Peak V̇o2was lower in patients (18.0 ± 0.6 vs. 33.3 ± 1.4 ml/min per kg, p < 0.0001), although both groups achieved a similar respiratory exchange ratio at peak exercise (1.15 ± 0.01 vs. 1.19 ± 0.03, p = 0.13). Quadriceps (582 vs. 652 cm2, p < 0.05) and total leg muscle CSA (1,153 vs. 1,304 cm2, p < 0.005) were lower in patients with chronic HF. Patients were weaker than control subjects (357 ± 12 vs. 434 ± 18 N, p < 0.005) and also exhibited greater fatigue at 20 min (79.1% vs. 92.1% of baseline value, p < 0.0001). After correcting strength for quadriceps CSA, significant differences persisted (5.9 ± 0.2 vs. 7.0 ± 0.3 N/cm2, p < 0.005), indicating reduced strength per unit muscle. In patients, but not control subjects, muscle CSA significantly correlated with peak absolute V̇o2(R = 0.66, p < 0.0001) and is an independent predictor of peak absolute V̇o2. Conclusions. Patients with chronic HF have reduced quadriceps maximal isometric strength. This weakness occurs as a result of both quantitative and qualitative abnormalities of the muscle. With increasing exercise limitation there is increasing muscle weakness. This progressive weakness occurs predominantly as a result of loss of quadriceps bulk. In patients, this muscular atrophy becomes a major determinant of exercise capacity.